Reducing sedation for pediatric body MRI using accelerated and abbreviated imaging protocols. - Ahmad, Rizwan; Hu, Houchun Harry; Krishnamurthy, Ramkumar; Krishnamurthy, Rajesh (Pediatric Radiology, 2018)
Magnetic resonance imaging (MRI) is an established diagnostic imaging tool for investigating pediatric disease. MRI allows assessment of structure, function, and morphology in cardiovascular imaging, as well as tissue characterization in body imaging, without the use of ionizing radiation. For MRI in children, sedation and general anesthesia (GA) are often utilized to suppress patient motion, which can otherwise compromise image quality and diagnostic efficacy. However, evidence is emerging that use of sedation and GA in children might have long-term neurocognitive side effects, in addition to the short-term procedure-related risks. These concerns make risk-benefit assessment of sedation and GA more challenging. Therefore, reducing or eliminating the need for sedation and GA is an important goal of imaging innovation and research in pediatric MRI. In this review, the authors focus on technical and clinical approaches to reducing and eliminating the use of sedation in the pediatric population based on image acquisition acceleration and imaging protocols abbreviation. This paper covers important physiological and technical considerations for pediatric body MR imaging and discusses MRI techniques that offer the potential of recovering diagnostic-quality images from accelerated scans. In this review, the authors also introduce the concept of reporting elements for important indications for pediatric body MRI and use this as a basis for abbreviating the MR protocols. By employing appropriate accelerated and abbreviated approaches based on an understanding of the imaging needs and reporting elements for a given clinical indication, it is possible to reduce sedation and GA for pediatric chest, cardiovascular and abdominal MRI.